Feasibility Study of the Re-Attribution of Crime of Apartheid to Israel - Mostafa Fazaeli; Emad Oboudiyat (حقوق بشر)
According to Article 7 of the Rome Statute, the crime of Apartheid refers to actions, policies, and courses of conduct with the purpose of maintaining an institutionalized regime of systematic racism and racial domination. Based on this definition, the word "Apartheid" will not only refer to the historical regime of South Africa (1948-1994) but is also recognized as a crime against humanity on par with torture and slavery. Due to certain similarities in legal systems and roots of establishment, Israel and the Apartheid Regime of South Africa have been considered to be analogous in various international documents sponsored by the United Nations until 1991.This study aims to analyze the historical rationale behind this recognition and the reversal of course by the United Nations General Assembly, which was initiated with the revocation of A/RES/3379 resolution (the equation of Zionism with racism). Furthermore, in the light of recent developments on domestic and international levels, it seems several unaligned trends are gaining ground in this respect to reaffirm the previous attribution of the crime of Apartheid to Israel. Through using E-Library data and employing the descriptive-analytical method, the veracity of the said trends, their projection, and their perseverance will be further discussed in this paper.